HUBUNGAN BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ONLINE SHOP - rostini rostini; Syahribulan Syahribulan; Marin Toding k (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
This study aims to determine the relationship of brand image and product quality on online shop purchasing decisions. The sample in this study were 50 respondents who had made an online shop purchase. The sampling method used was purposive sampling method. The data analysis method used is qualitative analysis and multiple linear regression with the help of the SPSS 22.0 for windows application. The results showed that partially (t test) brand image and product quality were not related to online shop purchasing decisions. With the coefficient of determination R Square (R2) of 1.5% which means the decision variable is influenced by two independent variables namely brand image and product quality. While the remaining 98.5% is influenced by variables not examined in this study.